2012
DOI: 10.1603/ec12325
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of an Autocontamination Trap System to Manage Populations of Emerald Ash Borer (Coleoptera: Buprestidae) With the Native Entomopathogenic Fungus, <I>Beauveria bassiana</I>

Abstract: Emerald ash borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) is an invasive species from Asia that was discovered in North America Canada, in 2002. Herein, we describe studies to develop an autocontamination trapping system to disseminate Beauveria bassiana to control beetle populations. The standard trap for emerald ash borer in Canada is a light green prism trap covered in an insect adhesive and baited with (Z)-3-hexenol. We compared of green multifunnel traps, green intercept panel traps (both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Fluoncoated traps have also been shown to remain effective for several years following initial treatment (Graham and Poland 2012). Initial studies have also shown that ßuon coated multifunnel traps increase the catch of A. planipennis over Rain-X coated traps (Lyons et al 2012, Francese et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoncoated traps have also been shown to remain effective for several years following initial treatment (Graham and Poland 2012). Initial studies have also shown that ßuon coated multifunnel traps increase the catch of A. planipennis over Rain-X coated traps (Lyons et al 2012, Francese et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have demonstrated successful control of multivoltine coleopterans by combining microbial and chemical insecticides (Shapiro-Ilan et al 2011). Populations of Agrilus planipennis (Coleoptera: Buprestidae), an invasive Asian beetle recently discovered in North America, are controlled through auto-contamination trapping systems, which involve Beauveria bassiana (Balsamo) Vuillemin plus Z-3-hexenol (Lyons et al 2012). The most successful strategy for management of RPW has been found to be a combination of mass trapping, chemical treatments and biological control (Murphy & Briscoe 1999;Faleiro 2006;Gindin et al 2006;El-Sufty et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Auto-inoculation devices have been developed to infect coleopteran insects such as sap beetles (e.g. Carpophilus lugubris Murray) (Dowd and Vega, 2003), rhinoceros beetle (Oryctes rhinoceros (L.)) (Moslim et al, 2011) and emerald ash borer (Agrilus planipennis Fairmaire) (Lyons et al, 2012) in a strategy that uses attraction, contamination and release of insect pests for biological control. Auto-inoculation traps (AIT) have also been used on non coleopteran insects like fruit flies (Ceratitis cosyra Walker, C. fasciventris Bezzi and C. capitata (Weidemann)) (Dimbi et al, 2003) and tsetse flies (Glossina spp.)…”
Section: Introductionmentioning
confidence: 99%
“…al., 1995;Klein and lacey, 1999;Dowd and Vega, 2003). In this technique, the target pest must be attracted to an auto-inoculation trap in substantial numbers and allowed to exit the trap after contamination with the fungal spores to horizontally transfer the inoculums to the populations elsewhere (Lyons et al, 2012). Fungal auto-dissemination within a host population occurs as a result of activities and movements of the host (Scholte et al, 2004).…”
Section: Introductionmentioning
confidence: 99%